LAND ORGANIZATION AS AN IMPORTANT FUNCTIONAL CONSTITUENT OF THE LAND USE PLANNING - Stoiko, Н.; Kovalyshyn, О.; Kulikovska, О.; Tryhuba, А. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2022)
Land is the resource that is getting scarce in the world because it is subjected to excessive anthropogenic burden. It causes reduction of the area of agricultural lands, decrease of soil fertility, loss of forest lands and biodiversity. Such situation needs improvement of the available approaches to land use management at all levels. In Ukraine, the system of land use planning has experienced some changes which, at the local level, include development of a complex plan for the prospective use of the territorial community area. The article studies peculiarities of performance of the land organization works to ensure sustainable land use of rural territories outside settlements by focusing on the ecological constituent of land use. It is studied that the complex plan includes several topic chapters, which can be implemented by making decisions, performing works and measures of land management. A particular focus is made on the fact that the land use planning should consider the value of ecosystem services, which can be obtained from the resources and processes provided by the land natural ecosystems. The authors analyse some problems of exploiting agricultural lands in Ukraine proving the expediency of development of the measures on land organization to improve the land management system. A methodical approach to performing the land organization works while developing a complex plan of a community is proposed. The approach suggests five stages: preparation, analysis and assessment, making a plan (projects), implementation, monitoring and control. It is based on the assessment of land suitability for agricultural production, soil analysis, land degradation, social and economic factors influencing making decisions on land use and management of the natural resources on agricultural landscapes.